Public Economics and Finance - Açıkgöz, Bernur (IntechOpen, 2019)
To better understand the role and importance of government, it is important to try to comprehend all aspects of public economics and finance. This book covers many of these aspects and presents a core thesis that government is a fundamental instrument of the social welfare of communities. It provides the reader with a comprehensive overview of new era states, and answers the question, does the new era require new government policies? Over five chapters, authors from a variety of disciplines and methodological approaches cover topics such as welfare states and social policies, borrowing in the context of public debt theory, and new budgetary approaches. This volume is a valuable contribution to the field and will be appreciated by the global community of scholars.